Professional practice in caring for maternal grief in the face of stillbirth in two countries - Gisele Ferreira Paris; Francine de Montigny; Sandra Marisa Pelloso
ABSTRACT Objective: to understand professional care for maternal grief in the puerperium of stillbirth. Methods: a clinical-qualitative study with all the women who had stillbirths living in Maringá (Brazil) and participating in the Center d'Études et de Recherche in Family Intervention at the University of Quebec in Outaouais in Gatineau (Canada). Semi-structured interviews were carried out and the relevant aspects were categorized into themes. Results: the identified categories were: Assistance received in the puerperium with a focus on grief: hospital and outpatient environment, and Professional support in coping with maternal grief after fetal loss: with contact and memories, without contact and without memories and impossibilities of contact with the baby. Final considerations: the need for a multidisciplinary support and monitoring network for women who experienced fetal loss was evident. From this study, a routine of care for grief can be implemented in Brazil based on experiences in Canada.